DEFISIENSI COLLABORATIVE GOVERNANCE DALAM PENANGANAN PANDEMI COVID-19 DI INDONESIA - Martina Purwaning Diah; Ike Arni Noventi; M. Rizki Pratama (Journal Publicuho, 2021)
AbstractThe Covid-19 pandemic is a shared problem so it must also be resolved collectively. In the context of crisis, the role of the government must remain dominant, but also by opening the door to collaborative governance. Therefore it is vital to understand the dynamics of the collaborative governance process in dealing with the Covid-19 pandemic which of course is full of challenges and obstacles in the midst of uncertainty. Researchers use the literature study method to track various conditions in an effort to resolve a pandemic that involves inter-sectoral efforts, but researchers find important points that must be corrected so that the handling of the pandemic does not experience deficiencies in collaborative governance. So far, real action is needed in improving the responsiveness of policies, quality of regulations, data management, monitoring systems and coordination among sectors. Keywords: collaborative governance; covid-19; pandemic AbstrakPandemi Covid-19 merupakan persoalan bersama sehingga juga harus diselesaikan secara bersama-sama pula. Dalam konteks krisis pun sebenarnya peran pemerintah harus tetap dominan akan tetapi juga dengan membuka pintu kolaborasi bersama dengan antar sektor (collaborative governance). Oleh karena itu penting untuk mengetahui dinamika proses collaborative governance dalam menangani pandemi Covid-19 yang tentu saja penuh dengan tantangan, kendala dan hambatan di tengah ketidakpastian. Peneliti menggunakan metode studi kepustakaan untuk melacak berbagai kondisi dalam usaha menyelesaikan pandemi yang melibatkan usaha antar sektor akan tetapi peneliti menemukan poin-poin penting yang harus diperbaiki agar penanganan pandemi tidak mengalami defisiensi dalam collaborative governance. Sejauh ini perlu tindakan nyata dalam memperbaiki responsivitas kebijakan, kualitas regulasi, manajemen data, sistem pengawasan dan koordinasi antar sektor.  Kata Kunci:  collaborative governance; covid-10; pandemi